Preventing Early Childhood Marriage through Strengthening Community Da'iyah and Tutor Peer Majelis Ta’lim in Bone Regency - Sarifa Suhra; Rosita Rosita (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Child marriage remains a persistent issue in Bone County, as evidenced by the high number of cases reported in 2019. While there has been some reduction in child marriage due to government intervention and Unicef cooperation in select villages, the problem persists. NU Muslimat has implemented various strategies to raise awareness and prevent child marriage to combat this. The study employed the ABCD method and found that community service effectively raised awareness among majelis taklim members and their children. Furthermore, the da'iyah training produced professionals capable of counseling against child marriage, while the peer tutor training involved individuals who conducted counseling sessions and created awareness materials. As a result of these interventions, members of the community and students expressed strong determination to avoid child marriage, demonstrating the positive impact of NU Muslimat's initiatives.